AGRICULTURAL SPRAY DEPOSIT QUANTIFICATION METHODS - de Cerqueira, D. T. R. [UNESP]; Raetano, C. G. [UNESP]; Henrique, M. [UNESP]; do Amaral Dal Pogetto, F. [UNESP]; Prado, E. P. [UNESP]; Christovam, R. S. [UNESP]; Serra, M. E. [UNESP]; Almeida Costa, S. I. [UNESP] (Amer Soc Agricultural & Biological Engineers, 2012)
Spray deposit evaluations have been used in research as a tool to develop and improve pesticide application techniques. Lab tests were conducted to compare methods for deposit quantification using different tracers (Brilliant Blue food dye, copper and sodium ions, Rhodamine B, and tebuconazole) on different targets. The artificial targets, were more efficient in recovering the spray deposits, except when capturing Brilliant Blue dye. The copper tracer (Cobox (R)) and the fungicide gave us better results on artificial and natural targets. The results have also shown a good suitability for the use of Brilliant Blue, particularly on natural targets. The selection and reliability of quantitative analysis methods for spray deposits were dependent on the target nature (natural or artificial), tracer substance, and target-tracer interaction.
Keywords: Application technology; Tracer; Target